Pharmacometrics of dolutegravir and tenofovir: a quantitative approach to characterise drug-drug interactions, pharmacogenetics and optimise treatment - Kawuma, Aida (Department of Medicine, 2023)
Africa houses more than 50% of the 37 million people estimated to be living with HIV (PLWH). Although great strides have been made in increasing access to antiretroviral therapy, the number of new HIV infections remains high. In sub-Saharan Africa, co-infections of HIV, tuberculosis, and malaria are common because the three pandemics overlap considerably. Treatment of these co-infections is often challenging because of the potential for drug-drug interactions. Dolutegravir-based regimens are now the preferred first-line option for the management of HIV. Therefore, many African countries have transitioned most PLWH from efavirenz- to dolutegravir-based regimens. A fixed-dose combination containing dolutegravir, tenofovir, and lamivudine taken daily constitutes one of the most widely used regimens in Africa. In this thesis, we employ population pharmacokinetic modelling to optimise HIV treatment using data from healthy volunteers or PLWH, some of whom also have tuberculosis. We characterise dolutegravir pharmacokinetics, pharmacogenetics, and its drug-drug interaction with the antituberculosis drugs rifampicin and rifabutin and with the antimalarial drugs artemether-lumefantrine and artesunate-amodiaquine. We also describe the pharmacokinetics of tenofovir when dosed as either tenofovir disoproxil fumarate or tenofovir alafenamide in South Africans living with HIV. We found that rifampicin increases dolutegravir clearance more than twofold, leading to a reduction in its exposure. We confirmed that this interaction can be overcome with twice-daily dosing of 50-mg dolutegravir. We also demonstrate that a simpler regimen of 100 mg once daily may be sufficient. We also found that rifabutin decreases dolutegravir volume of distribution, but without an overall change in exposure. The interaction between dolutegravir and artemether-lumefantrine or artesunate-amodiaquine was not clinically significant, and no dose adjustment is required when these are co-administered. Lastly, we demonstrate that polymorphisms within the UGT1A locus affect dolutegravir exposure among Africans. For tenofovir, we created a joint model that describes its disposition when given either as tenofovir disoproxil fumarate or tenofovir alafenamide. In conclusion, by employing pharmacometric techniques, we were able to analyze and pool data from different studies, including sparsely sampled data, and run simulations to test and inform alternative dosing scenarios.